(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The material of the article can be used by specialists in the history of the Renaissance and gender studies, as well as scientists of other fields such as art history, philology, sociology, philosophy. In addition, it would be appropriate to include it in the history and culture courses of the Renaissance in order to comprehensively and deeply consider the socio-cultural processes of the fate of women in the works of writers of this period.